INVESTIGATION OF NEO ASTEROIDS 2006 VB14 AND 1986 DA - Eglitis, I. (Одеські астрономічні публікації, 2019)
566 positions and photometric observa- tions of NEO objects 2006 VB14 = Y5705 = 345705 and 1986 DA were obtained with Baldone Schmidt telescope in 2018 and 2019, to detecting rotation period and other physical characteristics. A Fourier transform was applied to determine the rotation period for asteroid 1986 DA=6178. Value 3.12 ± 0.02h was obtained. Observations confirm the previously obtained rotation period P = 3.25h for 2006 VB14.